TINGKAT KESUKAAN KONSUMEN TERHADAP IKAN CAKALANG (KATSUWONUS PELAMIS L.) ASAP YANG DIRENDAM DALAM EKSTRAK KULIT MANGGIS - Bulele, Abdala; Pongoh, Jenki; Reo, Albert Royke (Sam Ratulangi University, 2017)
The purpose of this study was to determine consumer acceptance of smoked skipjack (Katsuwonus pelamis L) pre-treated in a solution of mangosteen peel with a concentration of 3%, 4% and 5%, in various soaking time 15 min or 30 min. The results showed that the pH and moisture content were relatively constant. Based on sensory evaluation, smoked fish pre-treated with 5% mangosteen peel and soaked for 30 min had higher value of taste, odor, and texture attributes